High-Level Activation of Transcription of the Yeast U6 snRNA Gene in Chromatin by the Basal RNA Polymerase III Transcription Factor TFIIIC - Shivaswamy, Sushma (American Society for Microbiology, 2004)
Transcription of the U6 snRNA gene (SNR6) in Saccharomyces cerevisiae by RNA polymerase III (pol III) requires TFIIIC and its box A and B binding sites. In contrast, TFIIIC has little or no effect on SNR6 transcription with purified components in vitro due to direct recognition of the SNR6 TATA box by TFIIIB. When SNR6 was assembled into chromatin in vitro by use of the Drosophila melanogaster S-190 extract, transcription of these templates with highly purified yeast pol III, TFIIIC, and TFIIIB displayed a near-absolute requirement for TFIIIC but yielded a 5- to 15-fold-higher level of transcription relative to naked DNA (>100-fold activation over repressed chromatin). Analysis of chromatin structure demonstrated that TFIIIC binding leads to remodeling of U6 gene chromatin, resulting in positioning of a nucleosome between boxes A and B. The resulting folding of the intervening DNA into the nucleosome could bring the suboptimally spaced SNR6 box A and B elements into greater proximity and thus facilitate activation of transcription. In the absence of ATP, however, the binding of TFIIIC to box B in chromatin was not accompanied by remodeling and the transcription activation was ∼35% of that seen in its presence, implying that both TFIIIC binding and ATP-dependent chromatin remodeling were required for the full activation of the gene. Our results suggest that TFIIIC, which is a basal transcription factor of pol III, also plays a direct role in remodeling chromatin on the SNR6 gene.